“Blessed Are the Killers of Infants”—Understanding the Imprecation of Psalm 137 in Light of the Canonical Contexts of the Major Prophets - Park, Ryu (Journal for Semitics, 2020)
The imprecation of Psalm 137, “Blessed are the revengers and the killers of infants” (vv. 8–9) does not seem to be in conformity with the broader messages of the Psalter, “Blessed is the man who delights in the law of Yahweh (Ps 1:1–2) and who dwells in your house and ever praises you (Ps 84:5)” and of the Old Testament, “Do not take revenge and love your neighbours and foreigners (Lev 19:18; Deut 10:19).” However, this imprecation of infants-death can be interpreted and understood in the literary contexts of the Major Prophets that show intertextual connection with Psalm 137 in terms of the imprecation and judgment themes (Isa 13:15–18; Jer 51:20–23). Certain passages of the Major Prophets contain the oracles of judgments against Israel’s enemies that are announced throughout Isaiah and Jeremiah as if the psalmist’s imprecation is answered. God would destroy Judah’s enemy, Babylon, in order to restore Judah.